Exploration of Student Religious Tolerance in Universitas Negeri Padang - Arjoni Arjoni; Cece Rakhmat; Syamsu Yusuf; Ilfiandra Ilfiandra (Universitas Islam Negeri Sjech M. Djamil Djambek Bukittinggi, 2022)
This article describes the exploration of religious tolerance from the perspective of Universitas Negeri Padang (UNP; Padang State University) students. The research is motivated by the development of a diverse conception of religious tolerance based on authority of the state and the culture of local communities. Students are part of the academic community that are constantly in flux. However, the conception of religious tolerance from a student's perspective has not been developed comprehensively, so further studies are needed to understand how students explore religious tolerance at UNP. This research method uses a qualitative approach. The subject of this study are the active students across different study programs; they are also cross-organizations, cross-religious and cross-cultural. We have also selected the active lecturers registered at UNP. Sampling was conducted with snowball sampling technique. Data collection uses in-depth interviews and observation.. The data analysis technique uses descriptive analysis. The results of this study reveal the indicators of religious tolerance from the perspective of UNP students, namely, being open toward differences, having mutual respect, having independence in acting, and giving the freedom for people to carry out worship, and prioritizing positive interaction between individuals and interfaith groups. The results of this study can be used to construct student religious tolerance assessments.